2018
DOI: 10.1002/bmc.4227
|View full text |Cite
|
Sign up to set email alerts
|

A sensitive LC–MS/MS method for simultaneous determination of cabozantinib and its metabolite cabozantinib N‐oxide in rat plasma and its application in a pharmacokinetic study

Abstract: Cabozantinib (CBZ) is used for the treatment of progressive, metastatic medullary thyroid cancer. Its major oxidative metabolite is cabozantinib N-oxide (CBN), which contains a structural alert associated with mutagenicity, yet the pharmacokinetics studies lack the simultaneous investigation of CBN and dose proportionality. In the current study a simple LC-MS/MS method was developed and validated for the simultaneous estimation and pharmacokinetic investigation of CBZ and CBN in rat plasma. The analytes were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…However, M7 was eluted after parent. It is usually N-oxide-type metabolites that are eluted at a later time than the parent when oxidation occurs [38,39,40]. Therefore, M5 was presumed to be oxidized to dimethyl groups within the range suggested, whereas M7 was presumed to be oxidized to the nitrogen or more sterically hindered location in the structure.…”
Section: Resultsmentioning
confidence: 99%
“…However, M7 was eluted after parent. It is usually N-oxide-type metabolites that are eluted at a later time than the parent when oxidation occurs [38,39,40]. Therefore, M5 was presumed to be oxidized to dimethyl groups within the range suggested, whereas M7 was presumed to be oxidized to the nitrogen or more sterically hindered location in the structure.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, PK studies in human and rats revealed multiple peaks in the plasma concentration time profiles starting approximately 24 h after CAB administration. This phenomenon is most likely due to an enterohepatic circulation (EHC), but not finally confirmed yet [ 12 , 14 , 15 ], as also other causes, like absorption in deeper bowel sections or the irregular pattern of gastric emptying, might be conceivable [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…9,11−13 With regard to the elimination of CBZ, it is exposed to extensive metabolism in the liver to form cabozantinib N-oxide (CBN) with an 10-fold lower potency than CBZ, in which cytochrome P450 3A4 (CYP3A4) is primarily involved. 1,9,14,15 Previous studies have showed that CBZ AUC was associated with significant increase when enrollees suffered from mild/moderate hepatic impairment and when concomitantly used with ketoconazole (a CYP3A4 inhibitor), which indicates that the alternation of CYP3A4 activity has an evident impact on CBZ metabolism. 10,16 As the most abundant CYP450 enzyme in human liver, CYP3A4 has an extremely wide range of substrates, in charge of the oxidative metabolism of estimated 50% of clinically used drugs.…”
Section: Introductionmentioning
confidence: 99%
“…CBZ possesses a long terminal half-life (∼120 h) and higher exposure, in terms of 5.4-fold AUC and 3.6-fold C max following repeated daily dosing. , Of note, CBZ is characterized by moderately high interindividual variability in pharmacokinetics. , With regard to the elimination of CBZ, it is exposed to extensive metabolism in the liver to form cabozantinib N-oxide (CBN) with an 10-fold lower potency than CBZ, in which cytochrome P450 3A4 (CYP3A4) is primarily involved. ,,, Previous studies have showed that CBZ AUC was associated with significant increase when enrollees suffered from mild/moderate hepatic impairment and when concomitantly used with ketoconazole (a CYP3A4 inhibitor), which indicates that the alternation of CYP3A4 activity has an evident impact on CBZ metabolism. , …”
Section: Introductionmentioning
confidence: 99%